PENGARUH TATA KELOLA PERUSAHAAN DAN KUALITAS AUDIT TERHADAP AGRESIVITAS PAJAK - Niluh Maharani Safitri; Bambang Subroto (Fakultas Ekonomi dan Bisnis Universitas Brawijaya, 2022)
The study aims to analyze the effect of corporate governance and audit quality on tax aggressiveness. The corporate governance incorporates the elements of institutional ownership, managerial ownership, independent commissioners, and audit committee. The population of this study consists of all companies listed on Indonesia Stock Exchange (IDX) between 2019 and 2020 including 454 observable samples selected through purposive sampling technique. This study utilized the secondary data from the financial statements and annual reports of all companies listed on the Indonesia Stock Exchange (IDX) between 2019 and 2020, analyzed by multiple linear regression utilizing application of Statistical Product and Service Solution version 25. The results indicated that tax aggressiveness can be reduced by increasing audit quality and managerial ownership. Meanwhile, tax aggressiveness was not affected by institutional ownership, independent commissioners, and audit committee. This study implies that increasing the number of managerial ownership and the quality of external audits alleviates tax aggressiveness.